Evolution of phase stability and structural properties in CrFeNiTiV high-entropy alloy under high-temperature heat treatment conditions - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Lee, Hansung; Ahn, Byungmin (Materials Science and Engineering: A, 2023)
A novel equiatomic CrFeNiTiV high entropy alloy (HEA) was prepared by mechanical alloying (MA) and following spark plasma sintering (SPS). Further, the effects of heat treatment temperature on the phase, microstructure, and mechanical properties of HEAs were investigated. The results indicated the formation of a single body-centered cubic (BCC) phase after 30 h of MA. After SPS, it is found that the separation of a single phase into BCC, Ni3Ti, and TiC-rich phases, owing to the large atomic radius and mixing enthalpy of Ti with other elements. Compared with sintered HEA, the initial phases did not change after heat treatment at elevated temperatures, but the coarsening of phases was observed. The microscopic results confirmed that all phases are homogeneously distributed with good interfacial bonding after heat treatment at 1000 °C. The hardness and elastic modulus of HEA increased with increasing heat treatment temperature up to 1000 °C, due to increased precipitation of Ni3Ti and TiC-rich phases and then slightly reduced for the sample heat treated at 1100 °C HEA owing to the coarsening of existing phases. The creep displacement was reduced for the heat-treated HEAs compared to the SPS sample, suggesting improved creep resistance after heat treatment. In addition, an artificial neural network was used to predict the hardness behavior of heat-treated HEAs, and it exhibited an excellent accuracy of about 93.4%. Therefore, the present study provides valuable insights into the phase stability and mechanical properties of HEAs suitable for high-temperature applications.
Keywords: After-heat treatment; Coarsenings; Effect of heat treatments; Heat treatment conditions; Heat treatment temperature; High entropy alloys; High temperature heat treatment; Mechanical behavior; Rich phase; Spark-plasma-sintering; Artificial neural network; High entropy alloy; Mechanical behavior; Phase stability; Powder metallurgy